The Neojihadist Cell as a Religious Organization: A Melbourne Jema'ah Case Study. (19th July 2017) - Lentini, Pete
Abstract : Notwithstanding significant macro-level research into neojihadist groups like al-Qaeda and DAISh, and their theology/ideology and tactics, there is significantly less information on micro-level actors, especially how they function as religious organizations. Drawing on rare (terrorism trial transcripts) and unique (listening device and telephone intercept transcripts of recorded terrorists' conversations) primary source materials, this paper examines how religious authority structures and agency structures functioned within a Melbourne jema'ah (group or cell) that Australian authorities disrupted in 2004-05. The paper argues that the jema'ah was a stable vehicle for transmitting religious authority, but its agency structures were under-developed. In cases wherein the two clashed, the former always prevailed. Its findings suggest that while religious organizations require strong religious authority structures, they also need effective agency structures to increase their opportunities to achieve their objectives. The study intends to contribute to new, enhanced understandings of both neojihadism and religious organizations.